A Review on Infectious Diseases in the 21st Century: Emerging Threats and Control Strategies - Abdulrahman Abdulaziz Alghamdi; Fatimah Ali Asiri; Abdulrahman Sulaiman A Abu Rabiah; Abdalla Saleh Hossain Al-Jarah; Mohsen Abdullah Saad Alotaibi; Muteb Abdullah Abdulrahman Aloraymah; Obaid Hameed Obaid Alharbi; Saad Abdulmohsen Nasser Mefairij; Abdulmajeedhammad almutairi; Dhaifallah Abdullah Allahyani; Samaher Mohammad Abdu Mohsen Almohaisen (International Journal of Medical Toxicology and Legal Medicine, 2024)
The 21st century has witnessed a profound transformation in the landscape of infectious diseases, driven by factors such as globalization, urbanization, climate change, and advances in technology. This study reviews the emerging threats of infectious diseases in the current century and evaluates the effectiveness of control strategies. Utilizing secondary data from diverse sources, including epidemiological databases, scholarly articles, and institutional reports, this review identifies key pathogens that have posed significant public health challenges, such as SARS-CoV-2, Ebola virus, Zika virus, and antimicrobial-resistant bacteria. The analysis reveals that while scientific advancements have facilitated rapid pathogen identification and vaccine development, the integration of technology in surveillance and diagnostics remains uneven across regions. Public health responses have also been hindered by socio-political factors, misinformation, and resource disparities. This study underscores the need for global collaboration in strengthening health systems, enhancing disease surveillance, and fostering adaptive strategies to mitigate the impact of infectious diseases. Furthermore, it advocates for policy frameworks that address the socioeconomic determinants of health and promote equitable access to healthcare resources. Through a synthesis of existing literature, this review aims to provide a comprehensive understanding of the dynamic challenges and strategic imperatives in managing infectious diseases in the 21st century.